Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

simplify the expression


Simplify The Expression class=

Sagot :

Answer:

[tex](17^{1/7} )^{7}[/tex] = [tex]17^{1/7 * 7 }[/tex] = [tex]17^{1}[/tex] = 17

hope this answer helps you.....

Answer:

17

Step-by-step explanation:

[tex](17^{\frac{1}{7} })^{7} = 17^{\frac{1}{7} } 17^{\frac{1}{7} } 17^{\frac{1}{7} }17^{\frac{1}{7} }17^{\frac{1}{7} }17^{\frac{1}{7} }17^{\frac{1}{7} } = 17^{\frac{1}{7}+\frac{1}{7} +\frac{1}{7}+\frac{1}{7}+\frac{1}{7}+\frac{1}{7}+\frac{1}{7} }=17^{\frac{7}{7} } =17^{1} = 17[/tex]